Colombia : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Context. Colombia's economic performance has been robust, underpinned by a very strong policy framework. Last year, real GDP grew by 4.3 percent, with low inflation. The country has a strong external position; the financial system is sound; and fiscal policy remains guided by a structural fiscal balance rule. The authorities intend to undertake an ambitious infrastructure program to be executed through public-private partnerships. Outlook and risks. Real GDP growth is projected to converge to potential (about 4 1\2 percent) in 2014, with inflation remaining within the 2-4 percent target range. The medium-term outlook is favorable, but risks are tilted to the downside. Colombia's important and growing ties with the global economy expose the economy to external risks. The most important sources of risk are a decline in oil prices, a deterioration in global financial conditions, and volatility from the normalization of monetary policy in the U.S. Near-term policy mix. The current policy mix is broadly adequate. As the ongoing economic recovery takes hold, monetary and fiscal policies are expected to shift to a more neutral stance. Colombia continues to rely on a flexible exchange rate to absorb external shocks. The authorities are also taking advantage of abundant foreign inflows, primarily foreign direct investment, to strengthen their international reserve buffer. Medium-term challenges. Colombia's key challenge is to sustain strong and inclusive growth with macroeconomic stability. To this purpose, it will be important to: (i) adhere to the fiscal consolidation plan, supporting it with revenue mobilization; (ii) address the infrastructure gap, without increasing fiscal risks; (iii) enhance the social security system by increasing coverage and improving equity, and containing health care costs; (iv) address remaining weaknesses in financial sector supervision; and (v) foster financial inclusion.